Development Strategy of Railway Traffic Infrastructure of the Republic of Croatia - Stipetić, Antun; Kreč, Srečko; Jenić, Vinko (Promet - Traffic&Transportation, 2004)
Considering the strategy of the railway traffic infrastructuredevelopment of the Republic of Croatia, the authors have alsoconsidered the restructuring of the railways in EU and Croatiawith the aim of insuring the very complex process being carriedout in everyday lives, full ofinterdependencies. First, the paralleldevelopment of the three networks that form the EU railwayssystem is given, together with their characteristics and futureroles. These are: the network of the Trans-European conventionalrailway line system, the high-speed railway line network(HS Net) and the network of railway lines intended prevailinglyfor the cargo transport (RTEFF, TEFFN). This is followed by apresentation of the basic aims of the strategic development ofrailways in Croatia and the overview of the conditions and thenecessary activities on the Corridor railway lines so as to preparethem for the integration into theE U traffic system. In elaboratingthe development strategy of the railway traffic infrastructurein Croatia, a summarised overview of the objectivesand the necessary activities is given, in order to renew the railwaynetwork, and to reconstruct it so that it could meet the requirementsset by the AGC andAGTC standards which are thecondition for the Pan-European railway lines.